2012
DOI: 10.4322/floram.2012.015
|View full text |Cite
|
Sign up to set email alerts
|

Influência da Qualidade das Lâminas no Desempenho Mecânico à Flexão de Painéis Compensados de Hevea brasiliensis

Abstract: Depois de concluída a fase principal de exploração comercial do látex (cerca de 30 anos), os plantios de seringueira apresentam-se como fonte alternativa de madeira para serraria e para outros produtos à base de madeira com valor agregado superior ao da lenha, tendência já consagrada em países do sudeste asiático. O presente trabalho teve como objetivo principal avaliar a influência do módulo de elasticidade dinâmico (E d ) das lâminas no desempenho mecânico à flexão de painéis compensados de Hevea brasiliensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
0
7
1
4
Order By: Relevance
“…E o uso final destes painéis é em função da espécie, da qualidade das lâminas, quantidade e do tipo de adesivo usado no processo produtivo (PALMA et al, 2012).…”
Section: Introductionunclassified
“…E o uso final destes painéis é em função da espécie, da qualidade das lâminas, quantidade e do tipo de adesivo usado no processo produtivo (PALMA et al, 2012).…”
Section: Introductionunclassified
“…Visual and acoustic nondestructive methods have been used previously to sort logs, lumber and veneers employed in the manufacturing of ply-based wood composites, as seen in several works [10][11][12][13][14][15]. Wang et al [15], while studying ultrasonically (US) rated veneer from red maple, found a positive relationship between veneer US variables and LVL billet stiffness and strength.…”
Section: Introductionmentioning
confidence: 99%
“…The method used for this differentiation was the visual grading which, according to Lara Palma et al (2012), is performed by industry based on type, quantity and dimensions of the defects found in the veneers. It has been established by industrial practice because there is no specific standard for this wood species.…”
Section: Methodsmentioning
confidence: 99%